Challenges facing independent multihospital healthcare technology management systems. - Clark, J.T (IEEE Engineering in medicine and biology magazine)
Independent, multihospital clinical engineering organizations have existed for 30 years. The clinical engineering profession has changed its focus over this time from equipment safety and control to healthcare technology management. Challenges faced by the professional have included cost pressures, outsourcing, and medical device industry changes. This paper describes an enduring independent, nonprofit, multihospital clinical engineering organization, the Technical Services Program (TSP) at the University of Vermont, which shows a successful adaptation to challenges. As part of TSP's five-year strategic plan, a strategy for changing these challenges into opportunities is part of the goal. Our clinical engineers have to be fluent in both information technology and biotechnology, follow trends in patient care technology and act accordingly, understand new customers and effectively deal with their technology problems, partner with manufacturers in technology support and planning, use failure analysis tools to effectively reduce technology-related patient incidents, and understand business and quality principles and apply them to make healthcare more cost effective. Current and future healthcare system changes are opportunities for the profession and fit well into the independent, multihospital mission of TSP.